2001
DOI: 10.1136/vr.149.17.526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maedi‐visna virus infection on milk production in dairy sheep in Greece

Abstract: BATSON, 0. V. (I1940) The function of the vertebral veins and their role in the spread of metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 6 publications
(8 reference statements)
2
11
0
3
Order By: Relevance
“…With regard to MV, prevalence was similar to other regions in Brazil (Lombardi et al 2009). Although SRLVs represent a concern in small ruminant exploration (Synge and Ritchie 2010), particularly in developing countries (Ploumi et al 2001;Yilmaz et al 2002), a minor effect on flock performance parameters has been described (Leitner et al 2010). The observed reduction in seroreactivity is an interesting finding and demonstrates that control programs may rapidly reduce its occurrence in affected areas.…”
Section: Discussionmentioning
confidence: 86%
“…With regard to MV, prevalence was similar to other regions in Brazil (Lombardi et al 2009). Although SRLVs represent a concern in small ruminant exploration (Synge and Ritchie 2010), particularly in developing countries (Ploumi et al 2001;Yilmaz et al 2002), a minor effect on flock performance parameters has been described (Leitner et al 2010). The observed reduction in seroreactivity is an interesting finding and demonstrates that control programs may rapidly reduce its occurrence in affected areas.…”
Section: Discussionmentioning
confidence: 86%
“…Unfortunately, serological methods aren't able to detect infected animals prior to seroconversion, and the result of the tests cannot be interpreted during the first 6 months of life because of passively acquired antibodies in non-infected offspring [16]. Presence of SRLV antibodies in ovine milk was detected by Ploumi et al [17], which indicated that MVV-seropositive sheep flocks are commonly associated with mastitis incidence. To our knowledge there is no study regarding the correlation between ovine mastitis and SRLV using molecular techniques in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…has a well-documented adverse effect in milk production (Snowder et al, 1990;Ploumi et al, 2001;Gelasakis et al, 2015). A survey performed in the United Kingdom has estimated that losses associated with Small Ruminant Lentivirus infections could be as high as 40% (Ritchie and Hosie, 2010).…”
Section: Significance In Adult Animalsmentioning
confidence: 99%